Uczeń zdolny a udział w olimpiadzie językowej - Spychała-Wawrzyniak, Małgorzata (Neofilolog, 2017)
Out of all foreign languages in Polish schools Spanish has achieved the most dynamic increase in popularity within the last few years. For those most fascinated with Spanish and its culture, there have been six editions of the National Spanish Contest in Poland, organised by the Modern Language Association of Poland in cooperation with Adam Mickiewicz University’s Institute of Romance Studies. The aim of the article is to present the assumptions and activities of the contest, targeted at the most gifted students, as well as to examine the ways in which the best ones among them prepared themselves, including the amount of time they spent analysing the program guidelines. We will try to address the question whether contest finalists are truly gifted students or merely ones with high language aptitude. Special focus will be placed on finalists’ work with their teachers. We are also going to consider possible challenges and problems, which they faced during the preparation process.